2021
DOI: 10.1590/1519-6984.195234
|View full text |Cite
|
Sign up to set email alerts
|

Technological potential of under-utilized starches from eight varieties of legumes grown in Cameroon

Abstract: Starch samples from eight legumes cultivars instar of one variety of Vigna unguiculata L. (Cowpea), one variety of Vigna subterrenea V. (Bambara groundnut) and six varieties of Phaseolus vulgaris L. (Common bean), grown in Cameroon were isolated, and their physicochemical and pasting properties were evaluated. The objectives of the study were to investigate the starch properties and processing characteristics of different bean varieties, and to establish the basic foundation of improving the functionality of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Starch contents of the isolated legume starches showed no significant difference and ranged from 82.06 g/100g for White bean to 88.40 g/100g for Yellow bean (Table 1). This revealed the high purity of legumes starches extract (Saho Tsaju Nguetcho et al, 2019). It's rather difficult to obtain pure starches from legumes, due to their high protein content.…”
Section: Total Starch Content (Tc) and Amylose Content (Ac)mentioning
confidence: 85%
See 1 more Smart Citation
“…Starch contents of the isolated legume starches showed no significant difference and ranged from 82.06 g/100g for White bean to 88.40 g/100g for Yellow bean (Table 1). This revealed the high purity of legumes starches extract (Saho Tsaju Nguetcho et al, 2019). It's rather difficult to obtain pure starches from legumes, due to their high protein content.…”
Section: Total Starch Content (Tc) and Amylose Content (Ac)mentioning
confidence: 85%
“…There was no increase of amount of water release from legume starch after the third FTC. The high stability of legume could be improved by their high amount of amylose content and their high water absorption capacity (Saho Tsaju Nguetcho et al, 2019). Indeed, the syneresis of starch gels is similar to the syneresis of waxy corn of 53.9% (Srichuwong et al, 2012).…”
Section: Freeze-thaw Stabilitymentioning
confidence: 99%
“…(2010) and Davari et al (2018), found compatible results. Carbohydrates in legume seeds are considered to have unique properties such as high temperature stability when compared to similar cereal or tuber starch depending on the legume species, but only a few of these seeds have been investigated (Tsaju & Yanou, 2021). Proper understanding of carbohydrates in different accessions of legumes could play an essential role in food industries which would improve food quality and framers' livelihoods as they make good market in food industries.…”
Section: The Lablab Value Chain Activitiesmentioning
confidence: 99%